Вы находитесь на странице: 1из 46

3

26.
26.1.

~a(M) S.
ZZ
=
an dS
(S)

ZZ

(~a, ~n)dS,

(26.1)

ZZ

~
(~a, dS),

(26.2)

(S)

:
=

(S)

~ , dS, dS
S ~n,
~a(M) S.
,
.
~n:
S , > 0,
, < 0.
~a ~n ~, ~, ~k:
~a = ax~ + ay~ + az~k,
~n = ~ cos + ~ cos + ~k cos ,
~a S

ZZ
(ax cos + ay cos + az cos )dS.
(26.3)
=
(S)

~a S (
~n), z = f (x, y).
1. ~n
cos = r
cos = r

1+

1+

f
x

f 2
x

f
y

2 ;

f
y

2 ;

f
y


f 2
x

122

3.

cos = r
2. ~n :

1+

1

f 2
x

f
y

2 .

~ f
+ ~k
~ f
x
y
~n = r
 2 .

f 2
1 + x + f
y

,
Oz , ,
Oz .
3. (~a, ~n):
ax f
ay f
+ az
x
y
(~a, ~n) = r

2 .

f 2
f
1 + x + y

S xOy ,

s
 f 2  f 2
dS = 1 +
+
dx dy
x
y

ZZ

(S)

(~a, ~n)dS =

ZZ
G

ax f
ay f
+ az
x
y
r
2  f 2
1 + f
+ y
x

ZZ 

ax

1+

 f 2
x

 f 2
y

dx dy


f
f
ay
+ az dxdy,
x
y

.. G.
S F (x, y, z) = 0, ~n

~n0 = r

~ F
+ ~ f
+ ~k F
x
y
z


2

F 2
+ F
+
x
y


F 2

(S), (V ) (. ???). ~n ,
(S).
. , ~a
. (S) : (S1 ) (S2 ). (S1 )
(S), ~a (

123

26.

), (S2 ) ,
~n ~a ( ,
).

ZZ
1 =
(~a, ~n) dS
(S1 )

, V S1 ,
ZZ
2 =
(~a, ~n) dS
(S2 )

, S2 V . , 1 > 0, 2 < 0.
ZZ
ZZ
ZZ
(~a, ~n)dS =
(~a, ~n)dS +
(~a, ~n)dS = 1 + 2 ,
(S)

(S1 )

(S2 )

,
ZZ
(~a, ~n)dS,
(S)

~a , , ( ) V , (S).
, (S)
, V (
) . , |1 | > |2 |
, . ,
V , , .. ,
- (, , , ..). ,
, |1 | < |2 |, .. . ,
, ( , ..).
V , , , ,
, 1 = 2 , S
.
, ,
, , .
,
.
26.2.

~a ,
. (S), V , :
ZZ
(V ) =
(~a, ~n)dS 6= 0.
(S)

124

3.

, V ( > 0),
( < 0), , > 0
() ,
< 0 . = 0, V ,
, ,
.
, , V , . ,
() , () .
~a S V ,
:
ZZ
1
(~a, ~n)dS,
(26.4)
V
(S)

S , .
(S) M ,
.. ,
ZZ
1
lim
(~a, ~n)dS.
(26.5)
V 0 V
(S)M

(S)

,
M.
, ~a M,
( divergentia ).
 ~a
S ( M) V , , , S
M, ~a M div ~a(M):
ZZ
1
div ~a(M) = lim
(~a, ~n0 )dS.
(26.6)
V 0 V
(S)M

(S)

, ~a , .
M. div ~a(M) > 0,
M , div ~a(M) < 0, M .
| div ~a| ().

.
26.1. ax , ay , az ~a (D)

ax
,
x

ay
,
y

az
,
z

div ~a (D)
div ~a =

ax ay az
+
+
.
x
y
z

(26.7)

125

26.

. cos , cos , cos


(S).
ZZ
ZZ
(~a, ~n0 )dS =
[ax cos + ay cos + az cos ]dS.
(26.8)
(S)

(S)

, :
ZZZ 
ZZ
P
Q R 
+
+
dV =
(P cos + Q cos + R cos )dS.
x
y
z
(V )

(26.9)

(S)

P = ax , Q = ay , R = az
(V ):
ZZ
ZZZ 
ax ay az 
(~a, ~n0 )dS =
+
+
dV,
x
y
z
(S)

(V )


ZZ
ZZZ
 a
ay az 
x
(~a, ~n0 )dS =
+
+
dV =

x
y
z M
(S)
(V )
 a

ay az
x
+
+
=
V,
x
y
z M

(26.10)

M (V ). (S)
M, M M,
ZZ
1
1  ax ay az 
+
+
div ~a = lim
(~a, ~n0 )dS = lim
V =
(S)M V
(S)M V
x
y
z
M

V 0

(S)

 a

M M

ay az 
+
+
.
x
y
z M
x

(26.11)

.

.
, , (
)
=

~ + ~ + ~k.
x
y
z

,
~a:


~
(,~a) =
~ + ~ + k (ax~ + ay~ + az~k) =
x
y
z
ax ay az
=
+
+
= div ~a.
x
y
z
div ~a
div ~a = (,~a).

(26.12)

, (26.11).

126

3.

1. : div ~c = 0, ~c =
c1~ + c2~ + c3~k .
,
c1 c2 c3
div ~c = div(c1~ + c2~ + c3~k) =
+
+
= 0.
x
y
z
2. ,
.. div C~a = C div ~a, C .
,
ay
az
ax
div C~a = div(Cax~ + Cay~ + Caz~k) = C
+C
+C
= C div ~a.
x
y
z
3. ,
.. div(~a ~b) = div ~a div ~b.
.
4. div(~a) = div ~a + (grad ,~a)
(~a) = (,~a) + (~a, ), .
,
(ax ) (ay ) (az )
+
+
=
x
y
z
ax
ay
az
+
ax +
+
ay +
+
az =
=
x
x
y
y
z
z
 a
ay az  


x
=
+
+
+
ax +
ay +
az = div ~a + (grad ,~a),
x
y
z
x
y
x
div ~a =

5. - (div ~r = 3).
,
x y z
div ~r = div(x~ + y~ + z~k) =
+
+
= 3.
x y z
6.
- : div[~c ~r] = 0.
,



~ ~ ~k


div[~c ~r] = div cx cy cz =
z y z
= div[~(cy z cz y) + ~(xcz zcx ) + ~k(ycx xcy )] = 0,

(cy z cz y) = 0,
x

(xcz zcx ) = 0,
y

(ycx xcy ) = 0.
z

127

26.

7.
: div(~c) = (~c, grad ).
,
div(~c) = div[cx~ + cy~ + cz~k] =
(cx ) (cy ) (cz )

=
+
+
= cx
+ cy
+ cz
= (~c, grad ).
x
y
z
x
y
z
26.3.

, , .
,
ZZ
ZZZ 
Q R 
P
(P cos + Q cos + R cos )dS =
+
+
dV
x
y
z
(S)

(V )

P = ax , Q = ay , R = az ,
ZZ
ZZZ 
ax ay az 
(ax cos + ay cos + az cos )dS =
+
+
dV
x
y
z
(S)

(V )

ZZ

(~a, ~n0 ) dS =

(S)

ZZZ

div ~a dV.

(V )

( , )
:
26.2. ~a (S) ~a (V ),
:
ZZ
ZZZ
(~a, ~n0 ) dS =
div ~a dV.
(26.13)
(S)

(V )

,
,
ZZZ
div ~a dV
(V )

,
ZZ
(~a, ~n0 ) dS.
(S)

26.1. ~r = x~ + y~ + z~k R H.

128

3.

. (26.13). div ~a

ax ay az
div ~a =
+
+
.
x
y
z
ax = x, ay = y, az = z,
ay
= 1,
y

ax
= 1,
x

az
=1
z

div ~a = 3.
ZZ
ZZZ
ZZZ
=
(~a, ~n0 )dS =
div ~a dV =
3dV = 3V = 3R2 H.
(S)

27.
27.1.

(V )

(V )

~a(N) .
(D), ~a,
( -) L. - t: ~r = ~r(t).
~a .
L A B, AB. A B n
(). Nk , ~a
~a(Nk )
(~a(Nk ), ~rk ),
~rk - ~r. :
n
X
(~a(Nk ), ~rk ).
k=1

,
L ,
lim

n
X

(~a(Nk ), ~rk ).

k=1

, , ~a AB
Z
Z
Z
(~a, d~r)
(~a, d~r)
(~a, dS),
L

(AB)

AB

S .
 ~a AB L
n
X
(~a(Nk ), ~rk )
k=1

129

27.

, 0.
,

(~a, d~r) = lim

(AB)

n
X

(~a(Nk ), ~rk ).

(27.1)

k=1

, .
(27.1) .
1.
~a = ax~ + ay~ + az~k,

~r = x~ + y~ + z~k,


(~a, ~r) = ax x + ay y + az z

(~a, ~r) =

ax x + ay y + az z.

, ( )
Z
Z
I=
(~a, d~r) =
ax dx + ay dy + az dz.
(27.2)
(AB)

(AB)

, .
2. d~r ~s0 |d~r| = dS, d~r = ~s0 dS.
(~a, d~r) = (~a, ~s0 ) dS = as dS,
as ~a . :
Z
Z
I=
(~a, d~r) =
as dS.
(27.3)
(AB)

(AB)

< /2, I > 0; > /2, I < 0; = /2, I =


0. , ~a AB L
~a
AB.
. L .
. ~a
,
Z
(~a, d~r)
(AB)

, , , , AB L.

130

3.

 ~a, L,
~a
I
C = (~a, d~r).
(L)

~a L
I
I
I
C = (~a, d~r) = as dS = (ax dx + ay dy + az dz).
(27.4)
(L)

(L)

(L)

. ~a
~v = ~v (M) .
.
, , , . M ~v(M) ~s0
(L), .. (~v, ~s0 ).
~a = ~v .
, ,
.
27.1. ~a = x3~ y 3~
~r = a cos t~ + a sin t~.
.
d~r = (a sin t~ + a cos t~)dt,

I=

Z
L

Z/2
(~a, d~r) = (x3~ y 3~)(a sin t~ + a cos t~)dt.
0

x = a cos t, y = a sin t
~a = a3 cos3 t~ a3 sin3 t~.
(27.3)

I=

Z
L

= a4

Z/2
~a d~r = (a3 cos3 t~ a3 sin3 t~)(a sin t~ + a cos t~)dt =
0

Z/2
0

Z/2
( cos3 t sin t sin3 t cos t)dt = a4
sin t cos t dt =
a4
sin t /2
= a4
= .
2 0
2
2

131

28.

28.


.
(D) ~a(M). M ~n0 ,
M. M P ,
~n0 . L,
M. L ~n0 ( . ??? ).
~a L:
I
C = (~a, d~r).
(L)

S , L.
I
1
(~a, d~r).
(28.1)
S
(L)

L. .
(S) M ,
I
1
lim
(~a, d~r).
(28.2)
(S)M S
(L)

(28.2). M
P.
(28.2),
M:
I
1
(M, ~n0 ) = lim
(~a, d~r).
(28.3)
(S)M S
(L)

(D), ~a, . M (D) P , ,


~a
ax
,
x

ay
,
y

az
z

(D).
~a L
I
ax dx + ay dy + az dz
(L)

(28.4)

132

3.

,
:
I
P (x, y, z)dx + Q(x, y, z)dy + R(x, y, z)dz =
(L)

ZZ h
 P
 Q P 
i
R Q 
R 
=

cos +

cos +

cos dS
y
z
z
x
x
y
(S)

:
I
ZZ h
az
ay 
ax dx + ay dy + az dz =

cos +
y
z
(L)
(S)
ZZ
 a


i
az
ay ax 
x
+

cos +

cos dS =
f (N) dS,
z
x
x
y

(28.5)

(S)

cos , cos , cos P , L S.


f (N)
,
I
ZZ
ZZ

(~a, d~r) =
f (N)dS = f (M )
dS = f (M )S,
(28.6)
(L)

(S)

(S)

M (S).
f (N)
I
1
f (M )S
(M, ~n0 ) =
lim
(~a, d~r) = lim
= f (M).
(28.7)
(S)M
S (S)M
S

(L)

M M

,
 a
ay 
z

(M, ~n0 ) = f (M) =


cos +
y
z
 a
 a
az 
ax 
x
y
+

cos +

cos .
z
x
x
y

(28.8)

(28.8)
:
~n0 = cos ~ + cos ~ + cos ~k







~ = az ay ~ + ax az ~ + ay ax ~k,
W
y
z
z
x
x
y

~ , ~n0 ) = |W
~ | |~n0 | cos = |W
~ | 1 cos ,
(M, ~n0 ) = (W

(28.9)

133

28.

~ ~n0 .
W
(28.9) , ~a , = 0
(cos = 1), .. M ~.
, W
~ M W
rot ~a (rotate . ).
 ~a rot ~a,

az ay

;
y
z
ax az
roty ~a =

;
z
x
ay ax
rotz ~a =

.
x
y
rotx ~a =

(28.10)

, ()
rot~a =

 a

 a
 a
ay 
az 
ax ~
x
y

~ +

~ +

k
y
z
z
x
x
y
z

(28.11)






rot ~a =

x
ax

y
ay

~k

z
az





= ~a.

(28.12)

~a = ax~ + ay~
rot ~a =

 a

ax ~
k.
y

(28.13)

, rot~a, ,
.
:
 ~a M rot ~a, ,
M ,
.
28.1.

.
1. :
rot ~c = 0,
~c = c1~ + c2~ + c3~k , c1 , c2 , c3 .

134

3.

,




rot ~c = rot(c1~ + c2~ + c3~k) =

x
c1

y
c2

~k

z
c3





= 0.

2. , ..
rot C~a = C rot ~a,
C .
,

~k
~
~



rot C~a = rot(Cax~ + Cay~ + Caz~k) =
=
x

y
z
Ca Ca Ca
x
y
z
Cay
Caz
Cax
Cay ~
Cax ~ Caz
k
~
~ +
~ +
~ +
k=
=
y
x
z
y
z
x
h a
 a
 a
ay 
az 
ax ~ i
y
z
x
=C

~ +

~ +

k = C rot ~a,
y
z
z
x
x
y

3. :
rot(~a ~b) = rot ~a rot ~b.
,



~
~


~
rot(~a + b) =
x
a + b a y
x
x
y + by

~
~k
~
~
k ~
~

+


x y z x y z
ax ay az
bx by bz


~k


=
z
az + bz




= rot ~a + rot ~b.

4.
rot(~a) = rot ~a + grad ~a,

(~a) = ~a + ~a.
5. -

rot[~c ~r] = 2~c,

~c = c1~ + c2~ + c3~k

,
~r = x~ + y~ + z~k.

135

28.
,


~ ~ ~k


~c ~r = c1 c2 c3 =
x y z
= c2 z~ + c3 x~ + c1 y~k c2 x~k c1 z~ c3 y~ =
= (c2 z c3 y)~ + (c3 x c1 z)~ + (c1 y c2 x)~k.

rot(~c ~r) = rot[(c2 z c3 y)~ + (c3 x c1 z)~ + (c1 y c2 x)~k] =




~k


~



=
= 2c1~ + 2c2~ + 2c3~k = 2~c.


x
y
z
c zc y c xc z c yc x
2
3
3
1
1
2

6. - :
rot ~r = 0,

~r = x~ + y~ + z~k.

,




rot ~r = rot(x~ + y~ + z~k) =

x
x

y
y

~k

z
z



z
x y

+
+
= 0,
=
y
z
x

7.
rot f (r)~r = 0.
4) rot ~r = 0.
2) 3) , , ~a

~k
~
~



rot ~a =
.
x y z
a
a
a
x

() rot ~a (. 2);
. ~
, E
, :
~ =
rot E

~
H
,
t

~ .
; t ; H
(rot) div [~a, ~b]:

136

3.

8.
div (~a ~b) = (~b, rot ~a) (~a, rot ~b).
,





div (~a ~b] =

28.2.

x
ax
bx

y
ay
by

z
az
bz



~
~ ~k

~a ~b = ax ay az .
bx by bz

P = ax , Q = ay , R = az
I
I
(~a, d~r) = ax dx + ay dy + az dz
(L)

(L)

(L)

ZZ h
az
ay 
ax dx + ay dy + az dz =

cos +
y
z
(S)

 a

 a
i
az 
ax 
x
y

+
cos +
cos dS,
z
x
x
y
I

(~a, d~r) =

(L)

ZZ

(rot~a, ~n0 )dS =

(S)

ZZ

rot~n0 ~a dS.

(28.14)

(S)

,
28.1 ( ). . ~a
L (S), (28.14).
,
rot ~a =

 a

ax ~

k
x
y
y

~n = ~k,
I
ZZ 
ay ax 
ax dx + ay dy =

dS.
x
y
(L)

(S)

(17931841 ., ).

137

29.

29.

,
,
.
Z
ZZ 
P
Q 
P dx + Q dy =

dS,
y
x
G

(L)


Q
P
=
.
y
x
.
. ,
.
 ~a(M) ,
rot ~a(M) = 0,

M E.

 u(M), ~a(M) = u(M),


~a, .
 G , , G, ,
G.
29.1. G ~a(M). :
1) ~a ;
2)
Z
(~a, d~r)

AB

A B, AB

AB,
G;
3) u(~x) , ~a(~x) = u(~x),
du = a1 dx + a2 dy + a3 dz;
4) , .. rot ~a = 0.
, .
1 2 3 4 1.
I. 1 2. A B ADB
G. ACB
, (. 11),
+ ADB
= .
ACB
I
(~a(~x), d~r) = 0,

. 11

138

3.

..

(~a, d~r) =

ACB

(~a, d~r) =

ADB

(~a, d~r).

BDA

II. 2 3. M0 , M
G. M0M M0 M.
Z
u(M) =
(~a, d~r)
M0M

M0M , G.
,
grad u(M) = ~a(M).
, , M = (x, y, z) N = (x + x, y, z):
Z
Z
Z
x u = u(N) u(M) =
(~a, d~r)
(~a, d~r) =
(~a, d~r).
M0 N

M0M

MN

x = x(t), y = y(t), z =
MN
z(t), t [x, x + x].
x u =

x+x
Z

x+x
Z

(~a(t), ~x (t))dt =

a1 (t, y, z)dt.

u(M)
u
1
= lim
= lim
x0 x
x0 x
x

x+x
Z

a1 (t, y, z)dt = a1 (x, y, z).

u/y = a2 u/z = a3 .
III. 3 4. ~a(M) = grad u(M),
rot ~a(M) = rot grad u(M) = 0.
IV. 4 1. rot~a(M) = 0.
,
Z
ZZ
~ = 0.
(~a, d~r) =
(rot~a, dS)

30.

(S)

, , grad , div ~a, rot~a .


. ,
.

30.

139

~ = grad ( grad );
G
~a u = div ~a (~a div ~a);
~ = rot~a (~a rot ~a):
~a W
~ = grad = ~ + ~ + ~k;
G
x
y
z
ax ay az
u = div ~a =
+
+
;
x
y
z


~k
~
~


~ = rot~a =
W
.
x y z
a
ay az
x

(30.1)
(30.2)

(30.3)

(.. (30.1)(30.3)
), ( ).
:
1) grad grad ;
2) grad div ~a; 3) grad rot~a;
4) div grad ;
5) div div ~a; 6) div rot~a = 0;
7) rot grad = 0; 8) rot div ~a; 9) rot rot~a.
, , ,
grad , grad grad
, grad rot~a. , rot div ~a , .
, . , , .
, div rot~a = 0.

div rot~a = ( ~a) = ( )~a = 0,

(30.4)

,
.
,
div ~a =

ax ay az
+
+
x
y
z

h a

 a
 a
ay 
az 
ax ~ i
x
y
div rot~a = div

~ +

~ +

k =
y
z
z
x
x
y
 az
ay 
 ax az 
 ay ax 
=

= 0.
x y
z
y z
x
z x
y
z

, rot grad = 0.
grad =

~ +
~ +
k
x
y
z

140

3.

rot~a =

 a

 a
 a
ay 
az 
ax ~
x
y
~ +

~ +

k
z
z
x
x
y






rot grad =


~k






=0


rot grad = = ( ) = 0
,
.
:


~  2 2 2
div grad = div
~ +
~ +
k =
+ 2 + 2.
x
y
z
x2
y
z

2 2 2
+ 2 + 2
x2
y
z
, , 2 :
div grad =

div grad = () = 2 ,

~ + ~ + ~k
x
y
z

2
2
2
+
+
.
x2 y 2 z 2

2 =

= 0

(30.5)

2 2 2
+ 2 + 2 =0
(30.6)
x2
y
z
. .

= f (x, y, z),
(30.7)
f (x, y, z) ,
.

2 2
+ 2 = 0.
(30.8)
x2
y
 (~x) E, E
.
:

141

30.

1)
= ax + by + cz + d;
2) = xyz;
3) = 1/r;
x
4) =
;
z+r
y
5) =
;
z+r
rz
6) = ln
.
r+z
:
1)
= ax + by + c;
2)
3)
4)
5)

= xy;
= x2 y 2 ;
= arctg y/x;
= ln r.

div grad , (30.5):


1. (C) = C,
(C) =

2 C 2 C 2 C
+
+
= C,
x2
y 2
z 2

C .
2. ( + ) = + ( );
3. () = + + 2 grad grad .
()
() = div[grad ],

() = (, [ grad + grad ]) =
= div(grad ) + grad grad + div(grad ) + grad grad =
= + + 2 grad grad .
4. ( ):
f (u) = f (u)u + f (u)(grad u)2 .
5. () :

f (r)
f (r)
=
.
r
r

(30.9)

142

3.

(30.9) .

1
f (r) = f (r) + f (r).
r

(30.10)

, , .
grad div ~a , ,
. rot rot~a.
. (30.6) .
~a ( ~a 2~a:
~a =

2~a 2~a 2~a


+
+
.
x2 y 2 z 2

(30.11)

~a ~, ~, ~k, ,
(30.11) .
 ~a(x, y, z) ,

~a, ..
~a = ax~ + ay~ + az~k,

(30.12)

2 ax 2 ax 2 ax
ax =
+
+
,
x2
y 2
z 2
2 ay 2 ay 2 ay
ay =
+
+
,
x2
y 2
z 2
2 az 2 az 2 az
+
+
.
az =
x2
y 2
z 2
,

~r = (x)~ + (y)~ + (z)~k 0,


~r = x~ + y~ + z~k,

.. - ~r .
~a, ~a ~a,
grad div ~a rot rot~a.
~a = grad div ~a rot rot~a.

(30.13)

, ~a .
~a (, ).
,
(30.11) (30.13):
1) C~a = C~a, C ;
2) (~a + ~b) = ~a + ~b;

143

31.

3) ~c = ~c,
~c = cx~ + cy~ + cz~k
;
4)
~r = ~r + 2 grad .
~a = 0 , ~a =
~b, ~b ,
.
~a = 0
ax = 0,

ay = 0,

az = 0,

~a, , .

31.

div () rot () :
I) , , , rot ~a 0;
II) () ,
div ~a 0;
III) , , , rot ~a 0, div ~a 0;
IV) : rot ~a 6= 0, div ~a 6= 0.
.
31.1.

() , rot ~a = 0
(D).
(D), ~a, -.
, rot ~a = 0
ay
ax
az
ay
ax
az
=
,
=
,
=
.
y
z
z
x
x
y
, () .
~a , ~a
u = (x, y, z)
(D), .. ~a = grad . , ~a = grad ,
rot ~a = rot grad = 0.
, rot ~a 0 ~a = grad .
, () () .
(x, y, z) .
.

144

3.

1. ~a

Z
(~a, d~r).
(L)

29.1
.
2. ~a :
I
(~a, d~r) = 0.
(L)

29.1.
 L ~a(~r), ~r E,
~a(~r)
.

,
dx
dy
dz
=
=
.
a1 (~r)
a2 (~r)
a3 (~r)

(31.1)

, , :
~r = ~a(~r).
(31.2)
 u(x, y, z) = C .
3. .
, ~a(M) = u u(x, y, z) =
C, M, ~a = grad u,
.
4. ( ).
, - (L) ,

I
(~a, d~r) = 0.
(L)

,
(31.2),
I

(L)

(~a(~r), d~r) =

Zt
0

(~a(~r(t)), ~r (t))dt =

Zt

[~a(~r(t))]2 dt > 0.

145

31.

31.2.

 ~a , ,
(D),
div ~a = 0.
, .
31.1. ~a(M)
G, ,
~a(M) .
. . (S)
G.
ZZ
ZZZ
~
=
(~a(~r), dS) =
div ~a dV = 0.
(S)

(V )

. = 0, (S) M.
ZZZ
div ~a dV = 0.
(V )

1
div ~a(M) = lim
V 0 V

ZZ

~ = 0.
(~a, dS)

(S)

, = 0.
,
(D) .
div ~a 0 (D),
ZZ
ZZZ
=
(~a, ~n0 ) dS =
div ~a dV = 0.
(S)

(V )

1. ( ), L,
, .. .
S = S1 + S2 . 31.1
ZZ
=
(~a, ~n0 ) dS = 0,
(S)

, ,
ZZ
ZZ
ZZ
(~a, ~n0 ) dS =
(~a, ~n0 ) dS +
(~a, ~n0 ) dS.
(S)

(S1 )

(S2 )

146

3.

ZZ

(~a, ~n0 ) dS =

(S1 )

ZZ

(~a, ~n0 ) dS.

(S2 )
()

~n0 ~n0 ,
,
ZZ
ZZ
()
(~a, ~n0 ) dS =
(~a, ~n0 ) dS.
(S1 )

(S2 )

 , (L).
2. .
S1 S2 , S3 S1 S2 .

ZZZ
ZZ
ZZ
ZZ
div ~a dV =
(~a, ~n0 ) dS +
(~a, ~n0 ) dS +
(~a, ~n0 ) dS.
(V )

(S1 )

(S2 )

(S3 )

, div ~a 0;
, ~a ~n0 .
(S1 ) ~n0
()
~n0 ,
ZZ
ZZ
()

(~a, ~n0 ) dS =

(S1 )

(~a, ~n0 ) dS,

(S2 )

.
3. , . , ,
( ).
2. , - M,
, ,
M .

. .
31.2. , ~a = rot ~b, .
. , ~a = rot ~b,
div ~a = div rot ~b 0

(30.4), .
, , .. .
~b .
,

147

31.

1) ( , );
2) ,
.. , .
31.3.

( )

 ( )
(D),
rot ~a = 0,

div ~a = 0.

, , .. , ().
, ~a = grad . ,
div ~a = 0,
div grad = 0 = 0.
.
~a , ,
:
~a = grad ,
= 0.
: ~a = 0.

~a = grad div ~a rot rot~a,


div ~a = 0, rot ~a = 0.
.
31.4.

,
rot ~a 6= 0,

div ~a 6= 0.

.
31.3. ~a

~ +C
~
~a =

~a = grad + rot ~b.

, ~a I, II III ~a. , ~a
, rot~a 0 ~a ; ~a , div ~a 0 ~a
.
grad, div, rot:
(grad ) = grad();
(div ~a) = div(~a);
(rot~a) = rot(~a).

148

31.5.

3.

1.
~ I,
.
.
M Oz:
p
= x2 + y 2.

~
~ = 2|I| (y~ + x~).
H
2
, . ,

~ = 0.
div H

Hx =

~
~
2|I|
2|I|y
y
=
H
=

;
x
2
x2 + y 2

~ =
div H

..

Hy =

2Ix
;
2

Hz = 0.

Hx Hy Hz
+
+
,
x
y
z

Hx
2Iy2x
4Ixy
= 2
= 4 ;
2
2
x
(x + y )

Hy
4Ixy
= 4 ;
y

Hz
= 0,
z

~ = 4Ixy 4Ixy = 0.
div H
4
4

, .
2.
+q1 . ~ , E
, M(x, y, z),
~ =
|E|

q1
,
r2

p
r = x2 + y 2 + z 2 M .
~ - OM.
~
E
~ = Ex~ + Ey~ + Ez~k,
E

~ cos = q1 x = q1 x ;
Ex = |E|
r2 r
r3
q
y
q
~ cos = 1 = 1 y ;
Ey = |E|
r2 r
r3

32. ,

~ cos = q1 z = q1 z .
Ez = |E|
r2 r
r3

149

~ = q1 x~ + q1 y ~ + q1 z ~k
E
r3
r3
r3

 q 
1
~
E = grad
.
r


3q1 x r
3q1 xy
Ex
= 4
= 5 ;
y
r y
r
Ey
3q1 y r
3q1 xy
= 4
= 5 .
x
r x
r
,
Ey
Ex
=
.
y
x
,
Ez
Ey
=
,
y
z

Ex
Ez
=
,
z
x

..
~ = 0,
rot E



~ = rot grad q1 = 0.
rot E
r

,
O(0, 0, 0):
~ = Ex + Ey + Ez .
div E
x
y
z
Ex , Ey , Ez :
Ex
(q1 x/r 3 )
r 2 3x2
=
= q1
;
x
x
r5
Ex
(q1 y/r 3)
r 2 3y 2
=
= q1
;
x
y
r5
Ez
(q1 z/r 3 )
r 2 3z 2
=
= q1
.
z
z
r5



~ = q1 3r 2 3(x2 + y 2 + z 2 ) = 0.
div E
5
r

~ = 0, div E
~ = 0,
, rot E
.. , .

150

3.

32.

32.1.

,
J() =

Zb

(32.1)

f (x, )dx.

 f (x, )
a x b, c d, > 0 > 0,
|x x | < | | <
|f (x , ) f (x, y)| < ,

x, x [a, b],

, [c, d].

32.1. f (x, ) a x b,
c d, (32.1)
.
. f (x, ) , .
x, x , > 0 > 0,
|x x | < | | < ,
|f (x, ) f (x , )|

.
ba

, x = x
Zb
Zb

Zb


|J( ) J()| = f (x, )dx f (x, )dx = [f (x, ) f (x, )]dx

Zb
a

|f (x, ) f (x, )|dx


ba

Zb

dx = .

, , J() .
32.2. f (x, ) f (x, )/ a x b, c d, (32.1) [c, d] ,
dJ()
=
d

Zb

f (x, )
dx.

.
J( + ) J()
.
0

J () = lim

(32.2)

151

32. ,

:
J( + ) J()
1
=

Zb

[f (x, + ) f (x, )]dx.

:
1

Zb
a

[f (x, + ) f (x, )]dx =

Zb

f
(x, + )dx.

(32.2):


Zb
1
f (x, )

dx =
[J( + ) J()]

Zb h
Zb


f (x, + ) f (x, ) i
f (x, + ) f (x, )

=
dx
dx.

f / [a, b] [c, d], , , .. > 0 , ,


x, x , [a, b] [c, d] , | | <
|x x | <
f (x , ) f (x, )

.

<

ba

/(b a) .
32.3. f (x, ) a x b, c d,
Zd

J()d =

Zd

J() =

Zb

f (x, )dx.

Zb

f (x, )dx,

(32.3)

.
32.3.1. f (x, )
32.2, a() b() [c, d],
d
d

Zb()
Zb()
f (x, )

f (x, )dx = f (b, )b () f (a(), )a () +


dx.

a()

a()

(32.4)

152

3.

.
, , , , . .
. , ,
, .
32.2.


J() =

f (x, )dx.

(32.5)

, ,
J() = lim

Zb

[c, d].

f (x, )dx,

 , > 0 b ,


Z
Zb



J() f (x, )dx = f (x, )dx <



a

[c, d].

32.1. ,
J() =

ex dx,

[0, 1],

, .
. , > 0 b
Z



ex dx < .


b

x = z
x1 = b z1 = b
dx = dz x2 = z2 = .

J() =

e dz = e

= eb .

(32.6)

153

32. ,

> 0 b ,
(32.6). , b = 1/b,
 1 


J
= e1 .
b

, < e1 b,
(32.6).
32.4 ( ). (32.5). g(x) 0 , |f (x, )| g(x)

Z
g(x)dx < ,
a

f (x, )dx,

Z
a

|f (x, |dx

. g(x) .
.
0 b ,

g(x)dx . , >

g(x)dx < .

Z
Z
Z


f (x, )dx |f (x, )|dx g(x)dx < .


b


Z


f (x, )dx <


b

[c, d] (32.5) .
.
32.5. f (x, ) a x ,
c d, (32.5) [c, d] ,
J() (32.5) [c, d].
32.6. f (x, ) f
a x , c d, (32.5)

Z
f (x, )
dx,

154

3.

J() [c, d] :
Z

J () =

f
dx.

(32.7)

32.7. 32.5, J()


[c, d],
Zd

Zd

J()d =

f (x, )dx.

, .
32.2.
Z

sin x
dx.
x

.
J(, ) =

ex

sin x
dx.
x

(32.8)

J() = lim J(, ).


0

(32.8) :
:
sin x


x
e

ex .
x
,
Z

ex dx,

1 x ,

ex

sin x
dx,
x

[0, 1]. ,
(32.8)
[0, 1]. (32.8) ,
J (, ) =

Z
0

ex cos xdx =

.
+ 2

(32.9)

155

33. - -

??. ,
J(, ) = arctg

+ C.

(32.8) , J(0, ) = 0, C = 0

J() = .
2

33.

- -

- -. - - ,
.
 x > 0 - ( )

(x) =

et tx1 dt.

(33.1)

. 12
(x)
. 12.
, - (33.1)
(x) = 2

e 2x1 d.

(33.2)

, , ,
(33.1), (33.2) (x)


Y
1
x  x/n
x
= xe
1+
e
,
(x)
n
n=1

d(x)
= lim
=
x1 dx

Z
0

ln t dt = lim

(33.3)

n
X
1

k=1


ln n

(33.4)

156

3.

, 0,5772. . .
(33.1), (33.2)
, t = ,
(33.3) .
 - ( )
Z1
B(x, y) = tx1 (1 t)y1 dt, x > 0, y > 0.
(33.5)
0

(33.5) -
Z/2
B(x, y) = 2 (sin )2x1 (cos )2y1 d,

(33.6)

(33.5) t = sin2 .
(x) B(x, y) (33.1), (33.2), (33.3), (33.5), (33.8)
, -.
- -
1 ( ). x > 0

(x + 1) = x(x).
(33.7)
. , (33.1):
(x + 1) =

tx et dt,

, U = tx , dU = xtx1 dt,
V = et , dV = et dt.

(x + 1) = tx et + z
0

tx1 et dt = x(x),

,
(33.3). , x 6= j, j = 0, ,
(1 + x)
=
(z)

zex
(1

+ x)e(1+x)

(1 + x/k)ex/k

k=1

=
[1 + (1 +

n=1

x)/n]e(x+1)/n
N

Y (1 + 1/n)x+1
Y 1 + x/k
1
=
lim
x lim
=
1 + x N
1 + (1 + x)/n N
(1 + 1/k)x
n=1

k=1

N
Y

1
(1 + 1/n)(x + n)
N +1
lim
= x lim
= x,
N N + 1 + x
1 + x N n=1
x+n+1

(33.1) (33.3).

157

33. - -

2.
(x)(y)
.
(x + y)

B(x, y) =

(33.8)

. I [1].
3. n
(n + 1) = n!

(33.9)

. (33.7) x = n.
(n + 1) = n(n) = = n!(1).

(1) =

et dt = 1,

(33.9) .
x y (x = n, y = m),
(33.8)
B(n, m) =

.h (n + m 1)! i
(n)(m + 1)
1
=1 m
=
,
n1
m(n + m)
(n 1)!m!
mCm+n1
Csl =

s!
l!(s l)!

.
, - , -
.
4. (x) , x = n, n = 0, , (x)
(. . 12).
., , [1].
5 ( ).
(z)(1 z) =

.
sin z

(33.10)

. (33.10) a < x < b.


(33.2)
(x) = 2

Z
0

eu u2x1 du,

158

3.

(1 x) = 2

ev v 12x dv.

, 0 < x < 1
(x)(1 x) = 4

2x1 u2

du

12x v2

dv = 4

Z Z
0

e(u

2 +v 2 )

 u 2x1
v

dudv.

: u = cos , v = sin , dudv = d d.

Z
Z/2
Z/2
2
(x)(1 x) = 4 e d (ctg )2x1 d = 2 (ctg )2x1 d.
0

tg2 =
Z/2
Z1 (1x)1

2x1
I = 2 (ctg )
d =
d,
1+
0

(??) = 1 x, , ,
I=

=
,
sin[(1 x)]
sin x

(. 33.8).
, (33.3). , z 6= n, n = , ,

1 Yh
x  x/n i1 Yh
x  x/k i1
1 Y
x2 1
(x)(x) = 2
1+
1 2
.
e
1
e
= 2
x n=1
n
k
x
n
n=1
k=1

(??)

x2 
sin x Y
=
1 2
x
n
n=1

,
x sin x

(x)(x) =

(x)(x) = (1 x)
(33.10).
6. (x) , .. x
(x) 6= 0.

(33.11)

159

33. - -

. . x0
(x). x0 6= j, j = 0, , (x)
1- , x0 6= j, j = 0, , (n + 1) = n!.

lim (1 x) = lim
=
= ,
xx0
xx0 (x) sin x
sin x0 lim (x)
xx0

sin x0 6= 0. , (1 x) x0
, 4.
.
7.
 2n + 1 

1
= n (2n 1)!!

2
2

 1 2n  (1)n 2n

=
.
2
(2n 1)!!

(33.12)

(33.13)

n = 0, .

. (33.7) x = (2n 1)/2.


 2n + 1 

 2n 1  2(n 1) + 1 
2n 1  2n + 1

1 =

=
2
2
2
2
2
1
(2n 1)(2n 3)  2(n 2) + 1 
1
=

=
(2n

1)(2n

3)

.
22
2
2n
2

(33.10) x = 1/2,
1

= ,
2
=
2
sin /2

..

1

,
2
.. (33.12) . (33.10) x = n + 1/2,
(33.12)

1
2


n =

(1)n
(1)n 2n
,
=
=
(1/2 + n) sin(n + /2)
(1/2 + n)
(2n 1)!!

.
.

1 
1
n+
n+
= (1)n .
2
2

(33.14)

. (33.12) (33.13),



(1)n 2n
1 1
1
n+

n = n (2n 1)!!
= (1)n ,
2
2
2
(2n 1)!!

160

3.

8.
(33.15)

B(x, y) = B(y, x).


(33.8).
9.
B(z, + 1) =

B(z + 1, ) =
B(z, );
z
+z

1
B(z, 1) = ;
z

(33.16)
(33.17)

1 
B(z, z) = 212z B , z ;
2

B(z, 1 z) =
.
sin z

(33.18)
(33.19)

(33.7) (33.8). ,
(33.17) ; (33.18) , (33.19)
.
10 ( ). n
n 1
1 2
1

(1) = (2)(n1)/2 .

(33.20)
n
n
n
n

(33.20) .
.

n 1
1 2

f (n) =
n
n
n

n 1 n 2
1
f (n) =

.
n
n
n

h 1 n 1ih 2 n 2i h n 1 1i


f (n) =

.
n
n
n
n
n
n
2

(x)(1 x) = / sin x,
f 2 (n) =

n1

= n1
.
Q
sin(/n) sin(2/n)
sin[(n 1)/n]
sin(k/n)
k=1

e2ik/n , k = 0, n 1, n- .

xn 1 = (x 1)(x e2i/n )(x e4i/n ) (x e(n1)2i/n ).

161

33. - -

n1
zn 1 Y
=
(z e2ik/n ).
z1
k=1

z 1,
n=

n1
Y
k=1

(1 eik n ).



n1
n1
n1
Y
Y
Y
n1

2

k
Y
ik n
ik 2
ik n ik n
ik
n1




n
n
) =
1e
e
e
e
=2
sin
.
(1 e


n
k=1

k=1

k=1

k=1

n = 2n1

n1
Y

sin

k=1

n1
Y

sin

k=1

n1 2n1
,
n

f 2 (n) =

k
,
n

k
n
= n1 .
n
2
1
f (n) = (2)(n1)/2 ,
n

.
11 ( ).

(x)(x + 1/2) = 2x1 (2x).


2
.
B(x, x) =

Z1
0

y =

1
4

tx1 (1 t)x1 dt =

1
2

1/2 t =

2
B(x, x) = x
4

2 ix1
1 1

t
dt.
4
2

2
t t = 1/2,

B(x, x) = 2

Z1 h

Z1/2h
0

2 ix1
1 1

t
dt.
4
2

u/2

Z1
0

u1/2 (1 u)x1du =

B
2x1

1
2


,x .

162

3.

-,
(x)(x)
1 (1/2)(x)
= 2x1
,
(2x)
2
(x + 1/2)

(x)(x + 1/2) =

22x1

(2x).

33.1. , -
(x) =

Z1 h
0

1 ix1
ln
dt,
t

x > 0.

(33.21)

. (33.21) t = eu . dt =
eu du, ln 1t = u u , t
. ,
Z1 h
0

Z0

1 ix1
ln
dt =
t

x1

(e

)du =

eu ux1 du = (x),

.
33.2. ,
Z

x4

5
dx =
.
4

(33.22)

. (33.22) x4 = u. x =
u1/4 dx = 14 u3/4 du. ,
Z
0

x4

Z
1
1
u
du =
dx = e
eu u 4 1 du =
4
4
0
0
1

1 1
=
=
+1 ,
4 4
4
u 1 3/4

33.3. -, ,
Z1

xk ln xdx =

1
,
(k + 1)2

k > 1.

. ln x = t
Z1
0

x ln xdx =

Z0

te(k+1)t dt.

163

33. - -

(k + 1)t = u. k + 1 > 0
Z1

1
xk ln xdx =
(k + 1)2

ueu du =

1
1
(2) =
,
2
(k + 1)
(k + 1)2

.
33.4.
J=

x2n eax dx,

a > 0.

. ax2 = t
(a > 0).
J =2

2n ax2

x e

dx =

1
an+1/2

tn1/2 et dt =

1  (2n 1)!!
= n+1/2 n +
= n n+1/2 .
a
2
2 a
1

33.5.
lim

ex dx = 1.

. x = t1/n dx =
1 1/n1
t
dt.
n
Z

xn

1
dx =
n

et t1/n1 dt =

1

1 1

=
+1 .
n n
n

- (x) x > 0
lim

ex dx = lim
n

1


+ 1 = (1) = 1.

33.6.
Z1
0

dx
1 xn

(n > 1).

164

3.

. x = t1/n (t > 0)
Z1
0

Z1
1
dx
1 1
1
1
1
1/n
n

(1 t)
dt = B , 1
=
t
=
n
n
n
n
n
1 xn
0
1 1

1 1 
1
=
.
=
n n
n (1)
n sin(/n)

.
33.7.
Z1
0

dx

1 x4

Z1
0

x2 dx

= .
4
4
1x

(33.23)

. x4 = t
 
1
Z1
Z1

dx
1
1 1 1 4
3/4
1/2
  ,

=
t
(1 t)
dt = B ,
=
4
4
4 2
1 x4
4 43
0
0
 
 
3
3
Z1



4
4
x dx
1
3 1
  =
  .

= B ,
=
4
4 2
1 x4
4 5
1
4

, (33.23).
33.8.
Z/2
J=
tg xdx,

6= n, n = , .

. tg x =

t (t > 0)

t(1)/2
1  + 1
+ 1
dt = B
,1
=
1+t
2
2
2
0
 + 1 
1
+ 1

1
=
.
1(1)
2
2
1 cos(/2)
1
J=
2

,
(33.6).
33.9. ,
Z/2
1 m + 1 n + 1
J=
sinm x cosn x dx = B
,
.
2
2
2
0

(33.24)

33. - -

. sin x =
1
2

Z1
0

165

t (t > 0).

1 m + 1 n + 1
t(m1)/2 (1 t)(n1)/2 dt = B
,
.
2
2
2

33.10.
Z1

J=

(1 + x)a (1 x)b dx,

a > 1,

b > 1.

(33.25)

. 1 x = 2t
J =2

a+b+1

Z1

tb (1 t)a dt = 2a+b+1 B(a + 1, b + 1).

(33.25) x = cos 2.
33.11.
ZZ
J=
xq y p d,
D

D , x + y = 1, p > 1,
q > 1.
. :

J=

Z1
0

Z1x
dx
xp y q dy.
0

q 6= 1,
1
J=
q+1

Z1

xp (1 x)q+1 dx =

1
1 (p + 1)(q + 2)
B(p + 1, q + 2) =
=
q+1
q + 1 (p + q + 3)

(p + 1)(q + 1)
B(p + 1, q + 1)
=
.
(p + q + 2)(p + q + 2)
p+q+2

33.12.
J=

Za
0

t2n a2 t2 dt,

a > 0.

166

3.

. t = a sin x, a > 0.
Z/2
J = a2n+2
sin2n x cos2 x dx.
0

(33.24),
1 3
(2n 1)!!a2n+2
2n+2 (n + 1/2)(3/2)
B n+ ,
=a
= n+2
.
2
2 2
2(n + 2)
2 (n + 1)!

2n+2 1

J =a

33.13. , |x|n + |y|n = an


(n > 0, a > 0).
. ,
(x 0, y 0). y = (an xn )1/n , 0 x a.

Za
Za
S = 4 ydx = 4 (an xn )1/n dx.
0


x = at1/n ,

dx = (a/n)t1/n1 dt.

4a2
S=
n

Z1
0

(1 t)1/n t1/n1 dt =

4a2  1
1  2a2 2 (1/n)
B
+ 1,
=
.
n
n
n
n (2/n)